Designing Interaction and Interfaces for Automated Vehicles : User-Centred Ecological Design and Testing - Stanton, Neville; Revell, Kirsten M. A.; Langdon, Patrick (CRC Press, 2021)
Driving automation and autonomy are already upon us and the problems that were predicted twenty years ago are beginning to appear. These problems include shortfalls in expected benefits, equipment unreliability, driver skill fade, and error-inducing equipment designs. Designing Interaction and Interfaces for Automated Vehicles: User-Centred Ecological Design and Testing investigates the difficult problem of how to interface drivers with automated vehicles by offering an inclusive, human-centred design process that focusses on human variability and capability in interaction with interfaces. This book introduces a novel method that combines both systems thinking and inclusive user-centred design. It models driver interaction, provides design specifications, concept designs, and the results of studies in simulators on the test track, and in road going vehicles. This book is for designers of systems interfaces, interactions, UX, Human Factors and Ergonomics researchers and practitioners involved with systems engineering and automotive academics._ "In this book, Prof Stanton and colleagues show how Human Factors methods can be applied to the tricky problem of interfacing human drivers with vehicle automation. They have developed an approach to designing the human-automation interaction for the handovers between the driver and the vehicle. This approach has been tested in driving simulators and, most interestingly, in real vehicles on British motorways. The approach, called User-Centred Ecological Interface Design, has been validated against driver behaviour and used to support their ongoing work on vehicle automation. I highly recommend this book for anyone interested, or involved, in designing human-automation interaction in vehicles and beyond." Professor Michael A. Regan, University of NSW Sydney, AUSTRALIA
Human Driver Post-Takeover Driving Performance in Highly Automated Vehicles Chapter 8.Validating Operator Event Sequence Diagrams: The Case of Automated Vehicle to Human Driver Takeovers Chapter 9. Breaking the Cycle of Frustration: Applying Neisser's Perceptual Cycle Model to Drivers of Semi-Autonomous Vehicles. Chapter 10. Semi-Automated Driving Has Higher Workload and Is Less Acceptable to Drivers Than Manual Vehicles: An On-Road Comparison of Three Contemporary SAE Level 2 Vehicles Chapter 11. The Iconography of Vehicle Automation -- A Focus Group Study Chapter 12.
Customisation of Takeover Guidance in Semi-Autonomous Vehicles Chapter 13.The Effects of Interface Customisation on Drivers' Takeover Experience in Highly Automated Driving Chapter 14.Accommodating Drivers' Preferences Using a Customised Takeover Interface Chapter 15.Modelling Automation-Human Driver Interactions in Vehicle Takeovers Using OESDs Chapter 16.Feedback in Highly Automated Vehicles: What Do Drivers Rely on in Simulated and Real-World Environments? Chapter 17. Can Allowing Interface Customisation Increase Driver Confidence and Safety Levels in Automated Vehicle TORs? Chapter 18.
The Effects of Customisable HMI on Subjective Evaluation of Takeover Experience on the Road Chapter 19.Accommodating Drivers' Preferences Using a Customised Takeover Interface on UK Motorways Chapter 20.Validating OESDs in an On-Road Study of Semi-Automated Vehicle to Human Driver Takeovers Chapter 21.Design Constraints and Guidelines for the automation-human interface.
OCLC-licensed vendor bibliographic record.
Keywords: Automated vehicles; Human-machine systems; Automobile driving -- Human factors; COMPUTERS / Computer Engineering; TECHNOLOGY / Engineering / Mechanical; TECHNOLOGY / Industrial Health & Safety